2007
DOI: 10.1007/s10663-007-9034-3
|View full text |Cite
|
Sign up to set email alerts
|

How do middle-aged children allocate time and money transfers to their older parents in Europe?

Abstract: Informal care, Private intergenerational transfers, J22,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 12 publications
2
84
0
4
Order By: Relevance
“…This results in the further exclusion of 984 dyads. The study sample also excludes 72 cases with unreliable values (i.e., age difference between parents and children is 12 years or less) following similar exclusion criteria used in previous research (e.g., Bonsang 2007). Thus, the final sample is restricted to 36,095 dyads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the further exclusion of 984 dyads. The study sample also excludes 72 cases with unreliable values (i.e., age difference between parents and children is 12 years or less) following similar exclusion criteria used in previous research (e.g., Bonsang 2007). Thus, the final sample is restricted to 36,095 dyads.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of net transfers between parents and children is defined as the monetary value of the sum of private transfers (e.g., money, care and help, and grandchild care) given minus the sum value of transfers received. Bonsang (2007) found that time and money transfers can act as substitutes. Attias-Donfut and Ogg (2009) suggest that age is associated with a gradual change in the pattern of transfer exchanges.…”
Section: Introductionmentioning
confidence: 99%
“…Another demographic factor that hinders adult-children is their housing situation (Bonsang, 2007) [19]. If an adult-child rents instead of owning a home, complications may occur like having enough space for their parents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If an adult-child rents instead of owning a home, complications may occur like having enough space for their parents. Income levels of the adult-children also play a large role in determining who cares for the elderly (Bonsang, 2007) [19]. On the condition that the elderly cannot afford any nursing home expenses, the adult-children may carry some of that financial burden.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation